2011
DOI: 10.1007/s00299-011-1183-y
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of sugarcane MYB transcription factor gene promoter (PScMYBAS1) in response to abiotic stresses and hormones

Abstract: The sugarcane (Saccharum officinarum) stress-related MYB transcription factor gene, ScMYBAS1, demonstrated induced response to water deficit and salt stress in our previous study. To elucidate its stress tolerance mechanism at the transcriptional level, we isolated and characterized the promoter (PScMYBAS1, 1,033 bp) flanking the 5' ScMYBAS1 coding region from the sugarcane genome. A series of PScMYBAS1 deletion derivatives from the transcription start site (-56, -152, -303, -442, -613, -777, -843, -1,033) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 27 publications
1
29
0
Order By: Relevance
“…6 Another MYB transcription factor from sugarcane (Saccharum officinarum), ScMYBAS1-3 showed induced response under water-deficit condition and salinity stress. 26 The MYB transcription factors AtMYB60 and AtMYB96 in Arabidopsis were shown to be functional through the ABA signaling network, regulating many plant specific responses like drought stress, disease resistance, 35 and stomatal movement, transcription factor gene, ScMYBAS1-3 showed enhanced expression in response to water-deficit and salt stress. 26 In soyabean (Glycine max), 156 MYB genes (GmMYB) have been identified and 43 of such genes showed altered expression level following treatment with ABA, salt, dehydration and cold stress.…”
Section: Myb Domain Proteins Act As Dna-binding Transcription Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Another MYB transcription factor from sugarcane (Saccharum officinarum), ScMYBAS1-3 showed induced response under water-deficit condition and salinity stress. 26 The MYB transcription factors AtMYB60 and AtMYB96 in Arabidopsis were shown to be functional through the ABA signaling network, regulating many plant specific responses like drought stress, disease resistance, 35 and stomatal movement, transcription factor gene, ScMYBAS1-3 showed enhanced expression in response to water-deficit and salt stress. 26 In soyabean (Glycine max), 156 MYB genes (GmMYB) have been identified and 43 of such genes showed altered expression level following treatment with ABA, salt, dehydration and cold stress.…”
Section: Myb Domain Proteins Act As Dna-binding Transcription Factorsmentioning
confidence: 99%
“…26 The MYB transcription factors AtMYB60 and AtMYB96 in Arabidopsis were shown to be functional through the ABA signaling network, regulating many plant specific responses like drought stress, disease resistance, 35 and stomatal movement, transcription factor gene, ScMYBAS1-3 showed enhanced expression in response to water-deficit and salt stress. 26 In soyabean (Glycine max), 156 MYB genes (GmMYB) have been identified and 43 of such genes showed altered expression level following treatment with ABA, salt, dehydration and cold stress. 17 More recent studies in rice (Oryza sativa) have established role of MYB gene OsMYBS3 in conferring cold tolerance (Su et al 2010), while the R2R3-MYB gene, OsMYB2, was shown to be involved in salt, cold, and dehydration tolerance in rice.…”
Section: Myb Domain Proteins Act As Dna-binding Transcription Factorsmentioning
confidence: 99%
“…Abiotic stresses, osmotic and salt stress are foremost environmental factors restrictive to sugarcane productivity in many parts of the world. As a consequence, efforts are in progress to explore the molecular adaptation mechanisms to stresses and to strengthen stress tolerance in this plant Prabu et al 2010;Prabu and Prasad 2011;Pagariya et al 2011Pagariya et al , 2012. This manuscript reports the isolation of SoMYB18, a R2R3-MYB transcription factor from sugarcane; further authenticates the role of SoMYB18 gene through physiological and biochemical estimations of stable transgenic tobacco plants overexpressing SoMYB18 gene driven by CaMV35S promoter under salt, cold, and osmotic stress conditions.…”
Section: Introductionmentioning
confidence: 91%
“…TaMYB1 and TaMYB2 participate in response to salt, ABA and osmotic stress, respectively, in wheat (Wang et al 2006). In sugarcane, the stress-associated MYB transcription factor ScMYB26/AS1 was activated while combating osmotic and salt stress (Prabu and Prasad 2011). Recently, Geethalakshmi et al (2014) identified 78 MYB transcription factor genes in sugarcane by computational searches.…”
Section: Introductionmentioning
confidence: 99%
“…For biofuel production, some approaches show interesting results, with lower biomass recalcitrance [51] and expression and accumulation of microbial cellulolytic enzymes in sugarcane leaves [52] to improve biomass hydrolysis. The most widely used promoters are the constitutive CaMV 35S and maize ubi1 , but sugarcane promoters have already been used or characterized, including tissue-specific [46,47] and responsive promoters [53]. However, sugarcane transformation is not a trivial task since problems such as transgene silencing frequently occur ([40,54] and references therein).…”
Section: Genomics Meets Biotechnology For the Improvement Of Saccharimentioning
confidence: 99%